2020
DOI: 10.1109/tsp.2019.2959226
|View full text |Cite
|
Sign up to set email alerts
|

Precise 3-D GNSS Attitude Determination Based on Riemannian Manifold Optimization Algorithms

Abstract: In the past few years, Global Navigation Satellite Systems (GNSS) based attitude determination has been widely used thanks to its high accuracy, low cost, and real-time performance. This paper presents a novel 3-D GNSS attitude determination method based on Riemannian optimization techniques. The paper first exploits the antenna geometry and baseline lengths to reformulate the 3-D GNSS attitude determination problem as an optimization over a non-convex set. Since the solution set is a manifold, in this manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As the solution set of the attitude matrix is a manifold, we formulate GNSS attitude determination as an optimization over Riemannian manifolds. An earlier study of manifold geometries has demonstrated the ability to develop efficient Riemannian algorithms with the capacity of offering accurate attitude estimations using the given carrier-phase ambiguities [36]. We demonstrate that Riemannian manifold optimization can also be utilized in the ambiguity resolution process to significantly improve the float solution.…”
Section: Introductionmentioning
confidence: 87%
“…As the solution set of the attitude matrix is a manifold, we formulate GNSS attitude determination as an optimization over Riemannian manifolds. An earlier study of manifold geometries has demonstrated the ability to develop efficient Riemannian algorithms with the capacity of offering accurate attitude estimations using the given carrier-phase ambiguities [36]. We demonstrate that Riemannian manifold optimization can also be utilized in the ambiguity resolution process to significantly improve the float solution.…”
Section: Introductionmentioning
confidence: 87%
“…2: Solve ( 22) to obtain RRM using the Riemannian algorithms. 3: Compute NRM using (23). 4: Initialize χ = χ 0 > 0 and k = 0.…”
Section: Integer Search Strategymentioning
confidence: 99%
“…M is a differentiable manifold, and the tangent space 35 of points scriptTboldxM is a linear space that can approximate the manifold M at each point xM. The tangent space is a limited dimensional linear space.…”
Section: Related Workmentioning
confidence: 99%
“…M is a differentiable manifold, and the tangent space 35 of points T x M is a linear space that can approximate the manifold M at each point x ∈ M. The tangent space is a limited dimensional linear space. From a geometric point of view, the manifold pattern can be estimated as an Euclidean space on a tiny local neighborhood, and the optimization direction of the model on the manifold, i.e., the Euclidean gradient mapping on the tangent space.…”
Section: Manifold Optimization: Definitions and Notationmentioning
confidence: 99%